Technology, Transparency, and Accountability: The Case of Smart Auditing in Makassar - Suryana, Putri Aulia Erpita; Yani, Andi Ahmad; Abdullah, Muhammad Tang (Universitas Andalas, 2024)
Electronic-Based Auditing (Smart Auditing) is the development of an internal monitoring model by the Regional Inspectorate of Makassar City to improve accountability and performance in managing activities and finances in all Regional Apparatus Organizations within the Makassar City Government. This program is an implementation of the Smart City Concept by the Makassar City Government which requires regional officials to apply technology and information to streamline the implementation of their main tasks and functions thereby increasing accountability and transparency as well as efforts to prevent various irregularities (fraud) that may occur in the process of implementing Organizational activities . The aim of this research is to describe and find out the results of the evaluation of the implementation of electronic-based programs (Smart Auditing) at the Makassar City Inspectorate.This research uses qualitative research methods through case studies. Data collection taken with observation, interview, and documentation of directly involved informants in implementation of that activities. The process of data analysis includes data reduction, data presentation, and conclusion. This research uses theory from the E-Auditing concept to see the level of success of electronic auditing with indicators of (1)the success of the target, (2)satisfaction to the program and (3)levels input and output. The results of the research conducted show that the implementation of the electronic-based inspection program or known as Smart Auditing at the Makassar City Inspectorate has been carried out well and has succeeded in achieving its objectives. However, there is still a need to improve facilities and infrastructure to support the achievement of goals, increase understanding in the field of Technology and Information for implementers and commitment and discipline from Regional Apparatus Organizations in the future.